Kajian Penerapan Konsep Arsitektur Hijau: Cluster Bahamas, Medan - Venny; Tessa Eka Darmayanti (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
The fast growing population of Indonesia in this 4.0 industry revolution influence the large demand of housing and without realizing caused negative impacts to the environment. The usage of eco-friendly materials is one of few aspect of sustainable architecture which is deemed important and could contribute in halting global warming. This research aims to get insights regarding the implementation of the  green architecture concept in Citraland Gama City Medan residence, and its impact on the environment. With qualitative research method, this research is expected to broaden knowledge and push architechs in Indonesia to contribute in developing housing based on green technology with the use of eco-friendly materials. The demand of gree housing is answered by Citraland Gama City Medan of PT. Ciputra. From the research one of the houses in the area is using local, recycled, prefabricated materials that could cut down cost and reduce material that has the potential to become waste so that it can positively impact the global warming issue, also having good impact on social and environment